Legal Study of the Existence of Electronic Evidence in Corruption Crimes - Sumilat, Rohyani Rigen Is; Ginting, Grenaldo (Gema Wiralodra, 2023)
The use of electronic information or documents as evidence in examinations of corruption cases is becoming increasingly important. Law Number 19 of 2016, concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions, regulates the use of information or electronic documents as valid evidence in the examination process in criminal trials in general. However, there is a lack of regulation regarding documents and electronic transactions as evidence in resolving criminal corruption cases in the Criminal Procedure Code (KUHAP). Therefore, efforts are needed to harmonize the ITE Law and the Criminal Procedure Code regulations regarding the use of information or electronic documents as evidence in corruption cases. The data used in this research is secondary data obtained from various literature sources such as books, laws, literature, and journals. Although the Criminal Procedure Code does not regulate the position of electronic evidence and the definition of evidence itself, Article 39 paragraph (1) of the Criminal Procedure Code states that objects that can be confiscated can be considered as evidence. However, Law Number 11 of 2008 concerning Information and Electronic Transactions and Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes recognize that electronic information or documents are valid legal evidence in the judge. Although the Criminal Procedure Code does not regulate the position of electronic evidence and the definition of evidence itself, Article 39 paragraph (1) of the Criminal Procedure Code states that objects that can be confiscated can be considered as evidence. However, Law Number 11 of 2008 concerning Information and Electronic Transactions and Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes recognize that electronic information or documents are valid legal evidence in the judge. Although the Criminal Procedure Code does not regulate the position of electronic evidence and the definition of evidence itself, Article 39 paragraph (1) of the Criminal Procedure Code states that objects that can be confiscated can be considered as evidence. However, Law Number 11 of 2008 concerning Information and Electronic Transactions and Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes recognize that electronic information or documents are valid legal evidence in the judge.